2012 IEEE Symposium on Biological Data Visualization (BioVis) 2012
DOI: 10.1109/biovis.2012.6378598
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty-aware visual analysis of biochemical reaction networks

Abstract: We present a visual analytics system that supports an uncertaintyaware analysis of static and dynamic attributes of biochemical reaction networks (BRNs). These are often described by mathematical models, such as ordinary differential equations (ODEs), which enable the integration of a multitude of different data and data types using parameter estimation. Due to the limited amount of data, parameter estimation does not necessarily yield a single point in parameter space and many attributes of the model remain u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…iVUN incorporates animation and linked line plots to visualize attribute dynamics (see Figure 2: dynamics). The animation allows the user to obtain an overview, e.g., to detect drastic changes, and to identify hubs of similar dynamics [6]. Thereby, the time-dependent means or standard deviations of the sample MathClass-open{vMathClass-open(αMathClass-close)MathClass-open(tMathClass-close)MathClass-close}α=1ntextsfsans-serifsMathClass-open(MathClass-open{xMathClass-open(αMathClass-close)MathClass-open(tMathClass-close)MathClass-close}α=1ntextsfsans-serifsMathClass-close) are mapped to the color of the respective link (node).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…iVUN incorporates animation and linked line plots to visualize attribute dynamics (see Figure 2: dynamics). The animation allows the user to obtain an overview, e.g., to detect drastic changes, and to identify hubs of similar dynamics [6]. Thereby, the time-dependent means or standard deviations of the sample MathClass-open{vMathClass-open(αMathClass-close)MathClass-open(tMathClass-close)MathClass-close}α=1ntextsfsans-serifsMathClass-open(MathClass-open{xMathClass-open(αMathClass-close)MathClass-open(tMathClass-close)MathClass-close}α=1ntextsfsans-serifsMathClass-close) are mapped to the color of the respective link (node).…”
Section: Methodsmentioning
confidence: 99%
“…To assess the utility of the individual visualization approaches and multiple linked views of iVUN , a qualitative user study with 10 domain experts was performed. A more detailed description of the design process as well as the design and results of the qualitative user study can be found in our previous work on the uncertainty-aware visual analysis of BRNs [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations